Pulmonary Embolism in Patient with Atrial Septal Defect and Deep Vein Thrombotic, The Case Report - Suryantoro M., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Pulmonary Embolism in Patient with Atrial Septal Defect and Deep Vein Thrombotic, The Case Report